2019
DOI: 10.2298/tsci180707218w
|View full text |Cite
|
Sign up to set email alerts
|

Line wind speed distribution model of rectangular tunnel cross-section

Abstract: Accurate monitoring of the tunnel wind speed plays a key role in achieving intelligent mine ventilation. Based on the difficulty faced in precise reflection of the average tunnel wind speed by point wind speed monitoring, this paper puts forward a method for accurate monitoring the tunnel wind speed by large-span ultrasonic linear wind speed sensor based on the method of the time difference. Besides, as to the core problem of representing the average section wind speed by section-linear wind speed, the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Experiments conducted by Li et al 23 indicated that the trend of airflow variation in the same roadway cross‐section had nothing to do with the airflow velocity, and the airflow velocity decreased gradually along the central line of the roadway to the roadway wall. Wei et al 24 put forward a method for accurate monitoring the tunnel airflow velocity by large‐span ultrasonic linear airflow velocity sensor based on the method of the time difference, and studied the distribution rules of section airflow velocity in rectangular tunnel with various support forms. Ligeza et al 25 established a three‐dimensional modeling of the structure of flow parameter fields in mine drifts, and obtained a set of data describing the parameters of flow in real transverse sections.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted by Li et al 23 indicated that the trend of airflow variation in the same roadway cross‐section had nothing to do with the airflow velocity, and the airflow velocity decreased gradually along the central line of the roadway to the roadway wall. Wei et al 24 put forward a method for accurate monitoring the tunnel airflow velocity by large‐span ultrasonic linear airflow velocity sensor based on the method of the time difference, and studied the distribution rules of section airflow velocity in rectangular tunnel with various support forms. Ligeza et al 25 established a three‐dimensional modeling of the structure of flow parameter fields in mine drifts, and obtained a set of data describing the parameters of flow in real transverse sections.…”
Section: Introductionmentioning
confidence: 99%